Conditioning of Surface Energy and Spray Application of Optical Waveguides for Integrated Intelligent Systems. (2016) - Hoffmann, Gerd-Albert; Reitberger, Thomas; Franke, Joerg; Overmeyer, Ludger
Abstract: Networks of optical waveguides allow for data transmission and sensing applications. Therefore, this technology is a key element for the integration of intelligent systems and structural health monitoring. Optical waveguides are the essential backbone to connect these structures. The flexible and high-resolution manufacturing of waveguides, also on three-dimensional substrates, is accomplished by a combination of two printing processes. In the first step, flexible substrates are conditioned by a printing technology with an adapted flexographic printing mechanism. To produce the optical waveguide itself, the Aerosol-Jet-Printing process of liquid polymer or varnish is used on pre-conditioned areas with hydrophobic or hydrophilic behaviour. Waveguides fabricated by this two-stage process reach parabolic cross sections with a minimum width down to 10 μm. This paper shows the mechanism for the use of the processes and latest results concerning the choice of materials, which allow the operability for this kind of manufacturing. We show the adaption of the local surface energy by the printing technology to achieve a self-configuration of UV varnishes for high-resolution waveguides.